2019
DOI: 10.1007/s13353-019-00522-x
|View full text |Cite
|
Sign up to set email alerts
|

Nutrigenomics in livestock—recent advances

Abstract: The study of the effects of nutrients on genome functioning, in terms of gene transcription, protein levels, and epigenetic mechanisms, is referred to as nutrigenomics. Nutrigenomic studies in farm animals, as distinct from rodents, are limited by the high cost of keeping livestock, their long generational distance, and ethical aspects. Yet farm animals, and particularly pigs, can serve as valuable animal models for human gastrological diseases, since they possess similar size, physiology, and nutritional habi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 76 publications
0
18
0
1
Order By: Relevance
“…Protein, fat and micro/macro-nutrient supplementation have been proposed as nutritional interventions applied during different growth and developmental stages of the animal (prenatal, neonatal, or post-natal) [ 158 , 159 ]. To elucidate the regulatory mechanisms of dietary protein levels on gene expression related to lipid metabolism, the study conducted by Zhao et al [ 53 ] showed that high dietary protein supply at 18% CP significantly reduced expressions of mRNA, enzyme activities and expression levels of key fat and marbling genes in pigs.…”
Section: Nutritional Genomics In Pigsmentioning
confidence: 99%
“…Protein, fat and micro/macro-nutrient supplementation have been proposed as nutritional interventions applied during different growth and developmental stages of the animal (prenatal, neonatal, or post-natal) [ 158 , 159 ]. To elucidate the regulatory mechanisms of dietary protein levels on gene expression related to lipid metabolism, the study conducted by Zhao et al [ 53 ] showed that high dietary protein supply at 18% CP significantly reduced expressions of mRNA, enzyme activities and expression levels of key fat and marbling genes in pigs.…”
Section: Nutritional Genomics In Pigsmentioning
confidence: 99%
“…There is no consensus on the cause of textural differences between wild and enhanced sea urchins and no previous work done on gene expression, comparing wild and enhanced sea urchin gonads. The latter is of interest as changes in nutrition can lead to phenotypic modifications through changes in gene expression profiles (Clarke & Abraham, 1992;Roche, 2006;Nowacka-Woszuk, 2020).…”
Section: Comm)mentioning
confidence: 99%
“…Understanding honey bee genotype-dependent responses to nutrition could enable marker-assisted breeding for improved health outcomes or the development of tailored feed supplements. The effects of diet have been studied in other livestock animals with reference to effective breeding and their influence on production traits and health (Nowacka-Woszuk 2020). The objective of this study was to test the effects of honey bee genetic variation on responses to natural and artificial diets.…”
Section: Introductionmentioning
confidence: 99%